Odpowiedź :
Niech x = 3; y =1
r^2 = x^2 +y^2 = 3^2 + 1^2 = 9 +1 = 10
r =√10
sin alfa =1/√10
tg alfa =1/3
sin alfa + 10*√tg alfa = 1/√10 + 10*√(1/3) =(√10)/10 +10/(√3) =
= (√10)/10 + [10*√3]/3 =[103*√3]/30
r^2 = x^2 +y^2 = 3^2 + 1^2 = 9 +1 = 10
r =√10
sin alfa =1/√10
tg alfa =1/3
sin alfa + 10*√tg alfa = 1/√10 + 10*√(1/3) =(√10)/10 +10/(√3) =
= (√10)/10 + [10*√3]/3 =[103*√3]/30
x = 3
y =1
r^2 = x^2 +y^2 = 3^2 + 1^2 = 9 +1 = 10
r = √10
sin alfa = 1/√10
tg alfa = 1/3
sin alfa + 10*√tg alfa
= 1/√10 + 10*√(1/3)
=(√10)/10 +10/(√3) =
= (√10)/10 + [10*√3]/3 =[103*√3]/30
y =1
r^2 = x^2 +y^2 = 3^2 + 1^2 = 9 +1 = 10
r = √10
sin alfa = 1/√10
tg alfa = 1/3
sin alfa + 10*√tg alfa
= 1/√10 + 10*√(1/3)
=(√10)/10 +10/(√3) =
= (√10)/10 + [10*√3]/3 =[103*√3]/30